Case report: Identification of atypical mantle cell lymphoma with CCND3 rearrangement by next-generation sequencing - Dai, Luomengjia; Zhang, Han; Chen, Wen; Xia, Yi; Qin, Shuchao; Shao, Yang; Li, Jianyong; Miao, Yi; Li, Bingzong; Zhu, Huayuan (Frontiers in Oncology, 2023)
The t(11;14) (q13;q32) translocation resulting in overexpression of cyclin D1 is the major oncogenic mechanism in mantle cell lymphoma(MCL). Most MCLs can be diagnosed based on morphological features, cyclin D1 expression, and IGH/CCND1 rearrangement. However, in some atypical cases where conventional FISH studies fail to detect IGH/CCND1 rearrangement or immunohistochemistry for cyclin D1 is negative, diagnosis can be difficult. Next-generation sequencing (NGS) may allow the identification of molecular alterations and assist in the diagnosis of atypical MCL. In this study, we reported a case diagnosed as asymptomatic MCL who presented with lymphadenopathy at the initial assessment. Lymph node biopsy was performed and revealed high Ki67 index. However, initial diagnosis of aggressive MCL was difficult since IGH/CCND1 rearrangement result was negative. Ultimately, by NGS we identified a rare CCND3 rearrangement in the patient, which lead to overexpression of cyclin D3, thereby facilitating the diagnosis of mantle cell lymphoma.